2018
DOI: 10.1111/ped.13464
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers in congenital diaphragmatic hernia: Left ventricular diameter and pulmonary hypertension

Abstract: Decrease in LVEDD and presence of PH are associated with poor prognosis. Also, PH was associated with mortality in CDH patients. Thus, outcome may be predicted on careful echocardiographic evaluation of the LV diameters and pulmonary pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…This technique was utilized because it is both the most consistently reported method for defining CDH-PH and the most pragmatic method for collecting CDH-PH data from multiple international institutions [17][18][19]. While numerous other indices for assessing PH have been reported, their reproducibility is unknown [20][21][22]. And, other composite echocardiographic findings (septal location, ventricular size, pulmonary artery size, or patent ductus arteriosus flow patterns) could offer valuable information but are infrequently captured.…”
Section: Discussionmentioning
confidence: 99%
“…This technique was utilized because it is both the most consistently reported method for defining CDH-PH and the most pragmatic method for collecting CDH-PH data from multiple international institutions [17][18][19]. While numerous other indices for assessing PH have been reported, their reproducibility is unknown [20][21][22]. And, other composite echocardiographic findings (septal location, ventricular size, pulmonary artery size, or patent ductus arteriosus flow patterns) could offer valuable information but are infrequently captured.…”
Section: Discussionmentioning
confidence: 99%
“…Additional relevant data were provided by one author [34]. Finally, 11 studies were included in this review (Table 1) [33,34,[36][37][38][39][40][41][42][43][44]. Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…There were signi cant variations in echocardiographic parameters among studies (Table 2). Two studies reported RV function [38,39], four reported LV function [33,34,37,43], and ve reported both RV and LV function [36,[40][41][42]44]. Two studies de ned LVD a priori [33,41].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations